Intravitreal injection of Huperzine A promotes retinal ganglion cells survival and axonal regeneration after optic nerve crush - Zhou, Lai-Yang; Chen, Di; Guo, Xin-Ran; Niu, Yu-Qian; Xu, Yong-Sai; Feng, Dong-Fu; Li, Tie-Chen (Frontiers in Cellular Neuroscience, 2023)
Traumatic optic neuropathy (TON) causes acute injury to the axons of retinal ganglion cell (RGC), resulting in loss of RGC and visual insufficiency. Several intrinsic and external factors can limit the regenerative ability of RGC after TON, subsequently leading to RGC death. Hence, investigating a potential drug that can protect RGC from various injuries and states of pathology after TON and enhance their regenerative capacity is a research hotspot. Here, we investigated whether Huperzine A (HupA), extracted from a Chinese herb, has neuroprotective effects and enhances neuronal regeneration following the optic nerve crush model. We first compared the three modes of drug delivery and found that intravitreal injection of HupA could promote RGC survival and axonal regeneration after ONC. Furthermore, we found that HupA can perform its neuroprotective and axonal regenerative effects through the mTOR pathway, which can be blocked by rapamycin. These results suggested that HupA provides neuroprotection and neuroregeneration of abilities by enhancing the mTOR activity, indicating promising application of HupA in the clinical treatment of TON.